Technology-Embedded Local Wisdom as a Digital Rubric for Reflective Mathematics Assessment in Vocational Education - Gusti Ayu Dessy Sugiharni; Putu Sabda Jayendra; Anak Agung Istri Putera Widiastiti; Gusti Ayu Dessy Sugiharni; Putu Sabda Jayendra (Jurnal Pembelajaran, Bimbingan, dan Pengelolaan Pendidikan, 2026)
Vocational training gives students the hands-on skills and thinking abilities they need to enter the job market. In math, reflective thinking is essential for keeping up with changing workplaces. Still, people have not yet fully developed assessment tools that combine local cultural elements with digital technology. The purpose of this study was to develop and validate a Digital Reflective Mathematics Assessment Rubric (DRMAR) that integrated technology-embedded local wisdom for students of vocational education. This study uses a Research and Development (R&D) design based on the ADDIE model involving 156 vocational school students in Indonesia. Systematic needs analysis, design, expert validation, and field testing developed the rubric. Seven experts (in mathematics education, vocational education, and assessment) conducted the validation and used inter-rater agreement to assess the reliability. The results of the validity analysis based on Aiken’s V coefficient obtained a score of 0.82 to 0.94 for all criteria in the rubric, so the results of the validity analysis are very valid. The analysis showed excellent inter-rater reliability (ICC = 0.87, p < 0.001). The field test results showed that 89.6% of students improved their reflective thinking skills, as assessed against the rubric criteria. 78.2% of students reached the “reflective practitioner” level on several assessment sessions. The DRMAR provides a valid and reliable measure of mathematical reflective thinking through technology-enhanced, culturally grounded tasks. This study offers a new integration of local wisdom in the form of digital rubric technology to fill the gaps in reflective assessment in vocational mathematics education.